Dampak Penggunaan Gadget Secara Berlebihan Terhadap Motivasi Belajar Siswa SDN 01 Banda Dalam - Lenggogeni Arrefa Sago; Suci Wulandari; Adrias Adrias; Fadilla Suciana (Lembag, 2025)
This study discusses how gadget use affects students' learning behavior and motivation at SDN 01 Banda Dalam, the results of interviews conducted with parents and teachers show that students who use gadgets too often tend to be easily distracted, have difficulty focusing while studying, and interact less with their surroundings. They are also more passive in class, less enthusiastic about doing assignments, and experience decreased curiosity. Other negative impacts include increased anxiety, sleep disturbances due to exposure to blue light, and signs of gadget addiction that affect academic achievement and social skills. To overcome this, parents limit the time spent using gadgets and increase children's social interactions, while teachers apply more interactive and interesting learning methods so that children are happy when learning. This study emphasizes the importance of cooperation between teachers and parents to limit and supervise gadget use so that children maintain a balance between digital entertainment and academic responsibilities.